(untitled) (Al-Mansour Journal, 2025)
Due to the increasing growth of data sent and received between parties, and how to protect it and keep it safe from tampering and theft, this led to the necessity of using and innovating techniques and algorithms that enhance the security of this data, especially sensitive data. Blockchain technology provides a reliable option for transferring data, especially sensitive data, securely due to its decentralized properties. However, there is still a challenge in how to maintain it in the face of continuous digital development. Non-fungible tokens (NFTs), one of the growing uses of blockchain technology, have evolved as digital ownership certificates that safely store a variety of data on a distributed ledger, This study offered a strategy for protecting a valuable, sensitive image and prove that a certain person is the rightful owner of it, The image encrypted, and then uploaded to the interplanetary file system (IPFS), hidden within a carrier image for added security, and then stored on the blockchain. This strategy would mitigate the issue of counterfeit photographs and nefarious individuals attempting to mimic the rightful owners of images or sensitive data. The results regarding encryption and embedding, which were as follows: PNG images retained higher quality after encoding than JPEG images. (PSNR: inf dB, MSE:0.0).